To solve the equation, we will first rationalize the denominators.
Given equation: sqrt(x)/(x*sqrt(3) + sqrt(2)) = 1/(2*x*sqrt(6) + 4)
Rationalizing the denominators, we get:
sqrt(x)(x*sqrt(3) - sqrt(2))/(x*sqrt(3) + sqrt(2))*(x*sqrt(3) - sqrt(2))
1/(2*x*sqrt(6) + 4) * (2*x*sqrt(6) - 4)
Now rewrite the equation using the rationalized denominators:
sqrt(x)(x*sqrt(3) - sqrt(2))/(x*sqrt(3) + sqrt(2))*(x*sqrt(3) - sqrt(2)) = 1/(2*x*sqrt(6) + 4) * (2*x*sqrt(6) - 4)
Now simplify the equation further:
x*[(x*sqrt(3))^2 - (sqrt(2))^2] = 2*x*sqrt(6) - 4
x*(3x^2 - 2) = 2*x*sqrt(6) - 4
3x^3 - 2x = 2*x*sqrt(6) - 4
Now, isolate the terms containing square root on one side and rest of the terms on the other side.
3x^3 - 2x - 2*x*sqrt(6) = -4
3x^3 - 2x - 2*x(2*sqrt(6)) = -4
3x^3 - 2x - 4sqrt(6)x = -4
Now, we can solve this cubic equation by either factoring, using numerical methods or by using appropriate software.
solve sqrt(x)/(x*sqrt(3) + sqrt(2)) = 1/(2*x*sqrt(6) + 4).
1 answer